The role of the skeletal muscle in atherosclerosis - Ferreira,Joana (2019)
The role of visceral obesity in atherosclerosis is well recognized by the medical community. On the contrary, the importance of skeletal muscle is almost unknown. Muscle is nowadays understood as an endocrine organ producing myokines with direct action in several physiological and pathological pathways, including atherosclerosis. The myokines reduce the formation of neointima, expression of inflammatory mediators, the recruitment of inflammatory cells and the formation of foam cells. Epidemiological studies are demonstrating the association between reduced muscle mass and cardiovascular atherosclerotic disease. Low muscle mass is associated with an increased prevalence of coronary heart disease, aortic calcification, carotid atherosclerosis, carotid intima-media thickness, intracranial artery stenosis and endothelial dysfunction. In this way resistance training, which increases the muscle size and strength may have a key role in atherosclerosis while endurance training alone might not. The time and type of protein intake by older adults may be critical to the maintenance of muscle mass and to the increase survival. The objective of this paper was to perform a review about the published literature in the last 13 years about the role of skeletal muscle in atherosclerosis.